2008
DOI: 10.1001/archotol.134.11.1144
|View full text |Cite
|
Sign up to set email alerts
|

Endolymphatic Sac Surgery for Ménière's Disease

Abstract: Objective: To analyze the results of primary and revision endolymphatic sac surgery for the treatment of Ménière's disease in patients who failed medical therapy.Design: Retrospective medical chart review.Setting: Tertiary referral center.Patients: Fifty-one adult patients with Ménière's disease who failed medical therapy.Interventions: Endolymphatic sac to mastoid shunts were performed. Revision sac procedures were performed in patients who developed clinically significant recurrent vertiginous spells 5 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 17 publications
(11 reference statements)
0
10
0
Order By: Relevance
“…Kitahara et al's study reported the results of patients who had endolymphatic sac drainage with and without insertion of steroid induced silastic and nonsurgical group. The vertigo control rates were similar in surgery groups with or without steroid, but hearing levels of steroid group had better long-term results than nonsteroid surgery group and nonsurgical group [172]. Their findings were also supported with review of Wetmore.…”
Section: Treatment Of Bilateral Meniere's Diseasementioning
confidence: 53%
“…Kitahara et al's study reported the results of patients who had endolymphatic sac drainage with and without insertion of steroid induced silastic and nonsurgical group. The vertigo control rates were similar in surgery groups with or without steroid, but hearing levels of steroid group had better long-term results than nonsteroid surgery group and nonsurgical group [172]. Their findings were also supported with review of Wetmore.…”
Section: Treatment Of Bilateral Meniere's Diseasementioning
confidence: 53%
“…The gentamicin injection may be performed without hospital admission, but the surgery requires hospitalization. There is a risk of hearing impairment following gentamicin injection and success of either treatment have been previously reported (2,3). Thus far there has only been one study concerning the treatment of Ménière’s disease by SSRIs (3).…”
Section: Introductionmentioning
confidence: 97%
“…Intratympanic gentamicin injections (1) or revision surgery (2) have been used for the treatment of patients with Ménière’s disease who have relapsed following endolymphatic sac surgery (EDS) or intratympanic gentamicin injection. Ménière’s disease is a condition with vertigo, tinnitus (ringing or buzzing noises in the ears) and progressive deafness.…”
Section: Introductionmentioning
confidence: 99%
“…For example, labyrinthectomy is the gold standard for vertigo control but is a destructive procedure resulting in a total loss of hearing [6]. ESS is effective with AAO classes A-B vertigo control of 64.5-77% and minimal risk to hearing [7][8][9].…”
Section: Introductionmentioning
confidence: 99%